Pancreatic duplication cyst misdiagnosed as distal pancreatic tumor: A case report and surgical approach - Zain, Lara; Sweity, Raghad; Alshawwa, Khaled; Bannoura, Sami; Jaber, Bashar; Abu-Zaydeh, Omar (Frontiers in Surgery, 2023)
Enteric duplication cysts (EDCs) are a benign and uncommon congenital malformation, with a nonspecific and extremely variable clinical presentation. EDCs associated with the pancreas are called pancreatic duplication cysts (PDCs). They are especially rare and can present with recurrent abdominal pain or even severe pancreatitis. These cysts often get confused with pancreatic neoplasms or pseudocysts, thus posing diagnostic and surgical challenges. Here, we report a case of a 20-year-old male patient with a 14-year history of recurrent abdominal pain and many hospital admissions, who had several imaging studies revealing a persistent focal heterogeneous lesion affecting the tail of the pancreas, surrounding a small pseudocyst. An ultrasound (U/S) guided biopsy was avoided due to the location of the mass. Surgical resection was carried out for the suspicion of malignancy and final pathology report showed benign findings while revealing that what was thought to be a pseudocyst turned out to be a gastric-type PDC, and after reviewing the available literature, we encountered 16 similar cases regarding misdiagnosing PDCs. We conclude that PDCs are very rare and have a variable clinical presentation as well as a likelihood of being confused with other pancreatic neoplasms. Therefore, PDCs need a high index of suspicion to avoid recurrent hospital admissions and unnecessary procedures due to the fact that sometimes a simple cystectomy is adequate.